Fingers to Sounds, Sounds to Fingers: Creative Interaction with Giacinto Scelsi’s Archival Materials as Means to Devise Performance Practices of His Music - Fusi, Marco (2023)
This article proposes a performance practice of Giacinto Scelsi’s music for strings, based on the study of the archival materials and musical instruments. The unusual creative strategy adopted by Scelsi was based on recordings of his free improvisations on the Ondiola and the subsequent transcription in conventional musical notation by hired assistants. The article argues that the participation of Scelsi’s assistants in the transcription process introduces implicit limitations in the traditional authoritative role of the score deriving from the transcriber’s musical aesthetics and understanding of the instrument, which are apparent in the result. To establish a new practice grounded on Scelsi’s recorded improvisations, the article proposes a two-fold approach, based on computer-assisted transcriptions of Scelsi’s recordings and a thorough investigation of his keyboard instrument, resulting in the sampling of the Ondiola’s resources. The experiential knowledge gathered in this phase allowed the author to imagine and creatively adapt to the violin instrumental strategies and technical approaches inspired by the Ondiola and apply them to computer-generated scores. The resulting interpretation is informed by knowledge of Scelsi’s creative routine and rooted in his tapes, while at the same time allowing performers creative freedom in expanding the technical and expressive possibilities of their instruments.
FRIS
1
Keywords: HIPEX: Historical Performance Practices of Experimental Music